Comic relief for anankastic conditionals - Fernando, Tim (Proceedings of the Amsterdam Colloquium, 2005)
Anankastic conditionals are analyzed in terms of events conceived as sequences of snapshots– roughly, comics. Quantification is applied not to worlds (sets of which are customarily identified with propositions) but to strings that record observations of actions. The account generalizes to other types of conditionals, sidestepping certain well-known problems that beset possible worlds treatments, such as logical omniscience and irrelevance. A refinement for anankastic conditionals is considered, incorporating action relations.